2010
DOI: 10.1071/mf09141
|View full text |Cite
|
Sign up to set email alerts
|

Management implications of juvenile reef fish habitat preferences and coral susceptibility to stressors

Abstract: In the Hawaiian Archipelago, shelter-dependent juvenile stages of many reef fishes and their coral habitats are increasingly put at risk by multiple anthropogenic stressors (e.g. overfishing and habitat loss, coral bleaching and sedimentation, respectively). We assessed coral bleaching (to identify relative susceptibility among growth forms) and the use v. availability of structurally complex and simple corals by juvenile reef fishes in Hawai'i. We use these data in a model that identifies habitats and resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…To date most studies on the importance of coral as habitat for juvenile reef fish have been based on experiments and field observations in the Pacific Ocean [26], [27], [28]. These studies have tended to focus on coral-associated species from prominent families such as, pomacentrids [27], [28], [29], chaetodontids [30] or gobies [9], on reefs within the Great Barrier Reef, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…To date most studies on the importance of coral as habitat for juvenile reef fish have been based on experiments and field observations in the Pacific Ocean [26], [27], [28]. These studies have tended to focus on coral-associated species from prominent families such as, pomacentrids [27], [28], [29], chaetodontids [30] or gobies [9], on reefs within the Great Barrier Reef, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have found that individual fish species are associated with particular habitat types and many species show ontogenetic changes in habitat use between adult and juvenile stages (Light & Jones, ; DeMartini et al ., ; Boaden & Kingsford, ). It is important to understand how habitat use can vary between different life stages of species as ontogenetic differences may require protection or individual management of various habitat types if the species is considered threatened.…”
Section: Discussionmentioning
confidence: 99%
“…The null hypothesis that H. whitei would not display a significant preference for a specific habitat was tested by comparing habitat availability with habitat use and determining habitat preference scores (Manly et al ., ; Light & Jones, ; Gladstone, ; DeMartini et al ., ). A point‐transect method was used to provide an estimate of the relative availability of each habitat type (Choat & Bellwood, ) where 20 transects measuring 30 m in length were haphazardly placed at each site.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, if fishing is not restricted, these largerbodied fishes are key targets for spearfishers and an increase in spearfishing is not accounted for in the model. Additionally, reef structure is likely to erode due to coral cover decline, preventing fish recruits and juveniles from hiding (Alvarez-Filip et al, 2009;DeMartini et al, 2010;Graham and Nash, 2013) and increasing their accessibility to their predatory fishes (Rogers et al, 2014), ultimately leading to a decline in reef fish productivity (Gratwicke et al, 2005). Therefore, we included two scalars related to the structural complexity a coral reef provides for: (1) the survival of both herbivorous and piscivorous fish recruits given by the relationship survival (Frec)…”
Section: Model Adaptationsmentioning
confidence: 99%